Escape routes : contemporary perspectives on life after punishment - Farrall, Stephen (Routledge, 2011)
Escape Routes: Contemporary Perspectives on Life After Punishment addresses the reasons why people stop offending, and the processes by which they are rehabilitated or resettled back into the community. Engaging with, and building upon, renewed criminological interest in this area, Escape Routes nevertheless broadens and enlivens the current debate. First, its scope goes beyond a narrowly-defined notion of crime and includes, for example, essays on religious redemption, the lives of ex-war criminals, and the relationship between ethnicity and desistance from crime. Second,